Social Perception in Infancy: A Near Infrared Spectroscopy Study. - Lloyd-Fox, Sarah; Blasi, Anna; Volein, Agnes; Everdell, Nick; Elwell, Clair E.; Johnson, Mark H. (Child Development)
A study utilized near infrared spectroscopy to examine functional activation in the social brain network in infancy. Data were obtained from 36 five-month-old infants in whom the hemodynamic responses to visually presented stimuli in the temporal lobes were measured. Findings revealed that a considerable increase in oxyhemoglobin was localized to two posterior temporal sites bilaterally, suggesting that these sites are involved in the social brain network in young infants. Findings are discussed in detail.